Under-ice limnology of coastal valley lakes at the edge of the Arctic Ocean - Antoniades, Dermot; Marois, Catherine; Klanten, Yohanna; Triglav, Katherine (Arctic Science, 2021)
The northern coast of Ellesmere Island in the Canadian High Arctic is undergoing amplified warming that parallels the rapid decline in Arctic Ocean sea ice extent, and many lakes in this region have already shown changes in response to warming. However, biogeochemical data from High Arctic freshwaters are limited, and mostly restricted to the short, ice-free period. We sampled four coastal lakes in Stuckberry Valley (82°54′N, 66°56′W) before the onset of spring melting in 2017, 2018 and 2019, to assess biogeochemical gradients in their water columns and characteristics of their surface sediments. Despite their proximity, there were large differences in limnological properties. The two shallower lakes closer to the ocean were oxygen deficient, whereas the two deeper, more distant lakes were more oxygenated. There were pronounced vertical gradients in major ions, metals, and nutrients that suggested large differences in the extent of anaerobic microbial processes among the lakes. Morphometry and dissolved oxygen were the overriding determinants of biogeochemical differences rather than position along this short ocean–inland gradient. The diversity of limnological conditions, and the sensitivity of these characteristics to changes in ice cover, underlines the need for further study of under-ice processes in extreme northern lakes. La côte nord de l’île d’Ellesmere, dans le Haut Arctique canadien, subit un réchauffement amplifié parallèle au déclin rapide de l’étendue de glace de mer de l’océan Arctique, et de nombreux lacs de cette région ont déjà affiché des changements en réponse au réchauffement. Toutefois, les données biogéochimiques des eaux douces du Haut Arctique sont rares, et la plupart du temps limitées à la courte période sans glace. Les auteurs ont échantillonné quatre lacs côtiers dans la vallée de Stuckberry (82°54′N, 66°56′O) avant le début de la fonte printanière en 2017, 2018, et 2019, afin d’évaluer les gradients biogéochimiques dans leurs colonnes d’eau et les caractéristiques de leurs ...